2015
DOI: 10.3389/fnsys.2015.00005
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted effects of noisy galvanic vestibular stimulation on manual tracking behavior in Parkinson’s disease

Abstract: Parkinson's disease (PD) is a neurodegenerative movement disorder that is characterized clinically by slowness of movement, rigidity, tremor, postural instability, and often cognitive impairments. Recent studies have demonstrated altered cortico-basal ganglia rhythms in PD, which raises the possibility of a role for non-invasive stimulation therapies such as noisy galvanic vestibular stimulation (GVS). We applied noisy GVS to 12 mild-moderately affected PD subjects (Hoehn and Yahr 1.5-2.5) off medication while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…This is beginning to occur in neurological contexts, such as daily right‐ear CVS for four weeks improving aphasic syndrome in left‐hemisphere stroke and disturbed arm position sense in poststroke neglect improving with galvanic vestibular stimulation (GVS) relative to sham stimulation (note that GVS does not appear to activate ACC) . There are also reports of GVS relative to sham GVS improving autonomic, motor and other functions in Parkinson’s Disease and other central neurodegenerative disorders, and early evidence that repeated CVS for several weeks can induce behavioural improvement in the minimally conscious state . Moreover, following reports of persistent pain and allodynia modulation by CVS in case studies and small case series (discussed in Miller and Ngo 3 ; see also McGeoch et al), a recent study examined 34 subjects with persistent (mostly neuropathic) pain and found that (i) a single session of right‐ear CVS induced small but statistically significant short term modulations of pain relative to a forehead icepack cold‐arousal control condition, (ii) three of nine subjects with allodynia had large, clinically significant CVS modulations, and (iii) CVS was well tolerated, with only one subject experiencing vomiting.…”
Section: Examining the Therapeutic Efficacy Of Vestibular Neuromodulamentioning
confidence: 99%
“…This is beginning to occur in neurological contexts, such as daily right‐ear CVS for four weeks improving aphasic syndrome in left‐hemisphere stroke and disturbed arm position sense in poststroke neglect improving with galvanic vestibular stimulation (GVS) relative to sham stimulation (note that GVS does not appear to activate ACC) . There are also reports of GVS relative to sham GVS improving autonomic, motor and other functions in Parkinson’s Disease and other central neurodegenerative disorders, and early evidence that repeated CVS for several weeks can induce behavioural improvement in the minimally conscious state . Moreover, following reports of persistent pain and allodynia modulation by CVS in case studies and small case series (discussed in Miller and Ngo 3 ; see also McGeoch et al), a recent study examined 34 subjects with persistent (mostly neuropathic) pain and found that (i) a single session of right‐ear CVS induced small but statistically significant short term modulations of pain relative to a forehead icepack cold‐arousal control condition, (ii) three of nine subjects with allodynia had large, clinically significant CVS modulations, and (iii) CVS was well tolerated, with only one subject experiencing vomiting.…”
Section: Examining the Therapeutic Efficacy Of Vestibular Neuromodulamentioning
confidence: 99%
“…A drug named levodopa is known as a standard traditional drug, accepted and proved to be ef icient in treating and managing PD. Unfortunately, this drug too has several side-effects like impairment in cognition and imbalance, leading to poor quality of life of patients with PD (Lee et al, 2015). It is the need of time that there should be some alternative therapy, either drug or technique to treat and manage PD, ensuring minimal to no side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Neurodegenerative disease like PD is also associated with the damage in the connections of interhemisphere as observed in any other neurodegenerative disorder. Vestibular stimulation had proved to improve the interhemisphere connections; this is the positive and signi icant (Lee et al, 2015). Certain studies had even emphasized that there was enhanced in the motor system functioning by vestibular stimulation when applied in PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is the second most common neurodegenerative disease ( Hirtz et al, 2007 ) that is often accompanied by degradation of motor performance manifested by symptoms such as tremor, rigidity, bradykinesia, akinesia (especially of the face), postural instability, and freezing episodes ( Lee et al, 2015 ). The affected individuals also experience cognitive difficulties, sleep disorder, and sensory deficits ( Litvan et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The vestibular nerve projects from underneath the mastoid bone to the cerebellar vermis through which the basal ganglia and the limbic system are activated, and the dopamine and noradrenaline levels are altered ( Pan et al, 2008 ; Kataoka et al, 2015 ). Consequently, it has been shown that in neurodegenerative disorders such as PD, GVS can improve motor functions ( Yamamoto et al, 2005 ; Pan et al, 2008 ; Lee et al, 2015 ; Samoudi et al, 2015 ). The effect of GVS on postural stability and balance has also been reported ( Pal et al, 2009 ; Kataoka et al, 2015 ; Samoudi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%